SISTEM INFORMASI REGISTRASI BIRO ADMINISTRASI AKADEMIK DAN KEMAHASISWAAN PADA IBI DARMAJAYA LAMPUNG - Neni Purwati (IIB Darmajaya, 2014)
Informatics and Business Institute (IBI) Darmajaya is one of the universities that aims to develop human resources through the disciplines of computer science and business. In duties and daily operations can not be separated from computer technology as a means to process data and information. As a college in the field of education, IBI Darmajaya develop a working system based on objects including the foundation, employees, lecture and students. As the development of higher education required a computerized system designed to speed up the process in the administrative services of student academic registration namely correspondence among others : Academic Leave, active the academic, Move Class, Department Move, Move PTS and making of the report and reduce the possibility of error in each process in case of queues in service Registration at the Biro Student Academic Administration IBI Darmajaya. With the implementation of this system in the form of an application program, the manufacture of correspondence or academic administration there will be no data errors, the reporting process and the data search can be done more quickly. This system can also improve productivity by increasing the quality of the work caused by increased work efficiency, saves work time and time decision making to solve a problem and is very helpful for the accuracy of the data when necessary speed in making reports.Keywords : Information Systems, Registration, Academic.